The development of Sun and Nadir sensors for a solar sail CubeSat - Loubser, Hanco Evert (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.